The relationship between short stature and psychosocial problems in primary school-age children - Salsabila Yasmine Dyahputri; Rini Sekartini (World Nutrition Journal, 2020)
Background: Short stature is a growth problem that are commonly found in developing countries. In Indonesia, the prevalence of primary school-aged children with short stature reaches 23.6% in 2018. Short stature in children is associated with psychosocial problems that are thought to be related to abuse, stigmatization, and social isolation faced by children. However, previous studies discussing this topic had mixed results and the number of studies has not been adequate.Objective: This study aimed to look for the relationship between short stature and psychosocial problems in primary school-aged children.Methods: A cross-sectional study design was used in primary school-aged children at SDN 01 Kampung Melayu. The study was conducted by comparing groups of children’s height and screening results for psychosocial problems using the PSC-17 questionnaire, which assesses three subscales of behavioral problems (internalizing, externalizing, and attention).Results: The prevalence of short statured children in SDN 01 Kampung Melayu reached 15.28%. The prevalence of children with psychosocial problems is 18.12% and the prevalence of short statured children with psychosocial problems is 22.73%. Analysis of association between short stature and psychosocial problems showed no statistically significant relationship, for general psychosocial problems (p=0.268), internalization subscale (p=0.532), externalization (p=0.400), attention (p=0.414), and PSC-17 total score (p=0.614).Conclusion: No significant relationship was found between short stature and psychosocial problems in primary school-aged children.